Disseminated Intravascular Coagulation With Excessive Fibrinolysis Following Diagnostic Prostatic Biopsy for Prostate Cancer - Ghallab, Muhammad; Ilyas, Usman; Tran, Lilian; Amin, Toka; Abdelmoteleb, Salma (Curēus (Palo Alto, CA), 2022)
The most common hematological disorder associated with prostate cancer is disseminated intravascular coagulation (DIC). In most cases, cancer patients with DIC have compensated fibrinolysis with a low incidence of bleeding. However, DIC with excessive fibrinolysis is a rare albeit life-threatening variant that can present with massive bleeding and is thought to occur due to the unique properties of neoplastic cells of prostate cancer that activate both procoagulant and anticoagulant pathways simultaneously. Depending on the shift of the intricate balance between the two forces, the net result can be either systemic micro- (DIC) or macro-thrombi, deep venous thrombosis (DVT) or pulmonary embolism, or a bleeding syndrome from excessive vicious activation of fibrinolysis.Here, we present a unique case of suspected prostate cancer who underwent a diagnostic prostatic biopsy. Subsequently, he developed massive hematuria requiring intensive care unit admission with multiple supportive blood products. Additionally, he was administered epsilon-aminocaproic acid with a prophylactic dose of heparin, with prompt resolution of bleeding. After stabilization, he was discharged with planned outpatient chemotherapy. However, he subsequently presented with lower extremity DVT within a week, which led to a stroke in the setting of a patent foramen ovale. This unique case report highlights how a change in the intricate balance of the coagulation cascade causes a polar shift in clinical presentation and complications.